Adaptability of expatriates’ leadership style to subsidiary organizational culture a comparative study between self-initiated and assigned expatriates - Macura, Jacqline (2021)
Researchers have agreed that organizational culture and leadership are very complex phenomena. Several studies have been conducted on the influence of leadership on organizational culture. However, the influence that organizational culture has on leader-ship has remained under-researched. Additionally, various studies have been conduct-ed on assigned expatriates ability to adapt their leadership style to a subsidiary organizational culture. However, numerous international experience studies indicate the gap of knowledge regarding other types of expatriates including self-initiated expatriates. This study aims to fill these two gaps by exploring factors influencing the (non-) adaptability of expatriates’ leadership styles to subsidiary organizational culture. By virtue of a qualitative analysis, the data collected from four different case groups of IKEA leaders was compared: Assigned expatriates, self-initiated expatriates, self-initiated transfers and natives. Here I report on nine factors (headquarters organizational culture, subsidiary organizational culture, people being led, motivation, personality traits, role and responsibilities concerning subsidiary, training and coaching leadership style, experience and situational challenges) that are interrelated as well as elaborate on their impact. My findings indicate that self-initiated expatriates and natives exhibit similar experience while self-initiated transfers and assigned expatriates also present similar experience. However, contrary to prior theorems that indicate that assigned expatriates would not adapt their leadership style to the subsidiary organizational culture, my findings indicate that IKEA assigned expatriates experience a fusion, meaning a mixture of both adaptation and non-adaptation. This finding advances the leadership literature by providing a different angle for further research and the inter-national experience studies by furthering the studies on the unresearched group of ex-patriates